2021
DOI: 10.3390/antiox10040509
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Brassinosteroid and Redox Signaling Contributes to the Activation of CBF Expression during Cold Responses in Tomato

Abstract: Brassinosteroids (BRs) play a critical role in plant responses to stress. However, the interplay of BRs and reactive oxygen species signaling in cold stress responses remains unclear. Here, we demonstrate that a partial loss of function in the BR biosynthesis gene DWARF resulted in lower whilst overexpression of DWARF led to increased levels of C-REPEAT BINDING FACTOR (CBF) transcripts. Exposure to cold stress increased BR synthesis and led to an accumulation of brassinazole-resistant 1 (BZR1), a central compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Reactive oxygen species (ROS) play a significant role in cold acclimation and their levels are increased in response to cold stress (Li et al, 2014 ; Zhang et al, 2020 ). It is well-known that ROS accumulation is harmful to the plant (e.g., Novák et al, 2013 ; Saxena et al, 2016 ), but recent reports indicate that ROS participate in the ICE-CBF pathway regulation and may (at a certain level) serve as signaling molecules and increase freezing tolerance (Wang et al, 2018 ; Devireddy et al, 2021 ; Fang et al, 2021 ). In addition, it has been shown that the activity of the CBF transcription factors is regulated by redox-mediated switching by TRX-H2, the thioredoxin translocated from cytoplasm to nucleus in response to low temperature (Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) play a significant role in cold acclimation and their levels are increased in response to cold stress (Li et al, 2014 ; Zhang et al, 2020 ). It is well-known that ROS accumulation is harmful to the plant (e.g., Novák et al, 2013 ; Saxena et al, 2016 ), but recent reports indicate that ROS participate in the ICE-CBF pathway regulation and may (at a certain level) serve as signaling molecules and increase freezing tolerance (Wang et al, 2018 ; Devireddy et al, 2021 ; Fang et al, 2021 ). In addition, it has been shown that the activity of the CBF transcription factors is regulated by redox-mediated switching by TRX-H2, the thioredoxin translocated from cytoplasm to nucleus in response to low temperature (Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies evidenced that BIN2 activities are down-regulated in the early stages of cold stress by HDA6 and later restored as a regulatory measure for CBF expression and levels [138]. Cold-induced BR also directly participates in the regulation of basal cold tolerance by increasing the expression levels of CBF1/2/3, COR15A, and COR47like transcripts in A. thaliana [139]. Consistent with these findings, studies in tomatoes have suggested a BR component, brassinazole-resistant 1 (BRZ1), that inducts the expression of CBFs.…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascade and Hormonal...mentioning
confidence: 94%
“…The activation of tomato ROS signaling pathway was achieved through the expression of RBOH1 , in which the gene was found responsible in triggering H 2 O 2 . The H 2 O 2 modulated the redox status in cold-stressed plants and increased BZR1 production and CBF genes transcription ( Fang et al, 2021 ). Further, Ca 2+ influx is also reported to be involved in the activation of RBOH1 , hence enhancing the production of ROS ( Kour et al, 2021 ).…”
Section: Early and Late Cold Stress Response By Transcription Factorsmentioning
confidence: 99%